Determination of the Zinc level in Environmental and Biological Samples in Baiji City by Atomic Absorption Spectrophotometer - Hasan Mohammed Hasan (Tikrit Journal of Pure Science, 2022)
This study was conducted to measure Zinc levels in environmental and biological samples. The method was tested with three types of samples, including soil, water, and human blood serum. In this method, 50 samples from each soil, water, and human blood serum were used. The water and soil samples were collected from the Baiji oil refinery, while the human blood serum was collected from the patients in the Baiji hospital. The total Zinc concentration in the environmental and biological samples was measured by atomic absorption spectrophotometry (AAS). The results of the Zinc determination were obtained from the samples taken from the soil for each site under examination. The following values showed the mean average concentration for each site, respectively. site 1 (15±3.5), site 2 (11.5±1.1), site 3 (14.5)  ±0.5), and site 4 (13.8±3.8) µg/g. Moreover, the Zinc concentration in the water samples was between 3-14.3 µg/ mL. The Zinc concentration in the blood serum samples of the control and the healthy group was 598 ± 32 µg/mL, and in the patient group was 450 ± 16 µg/mL.